The Public Library in the Bibliographic Network, 1st edition - Turock, Betty (Routledge, 2020)
This book, first published in 1986, focuses on valuable information to all public library professionals who have questions about their participation in bibliographic networks. Contributors provide insights into both the benefits and the costs of networking by libraries of varying sizes and geographic locations. The actual uses of networks, their costs (including initial and ongoing expenses), and staffing needs are clearly explained.